INOVASI APLIKASI E-RUSUN DALAM UPAYA PENINGKATAN PELAYANAN DI DINAS PERUMAHAN RAKYAT DAN KAWASAN PERMUKIMAN SERTA PERTANAHAN KOTA SURABAYA - Sari, Neni Novita; Pradana, Galih Wahyu (Universitas Negeri Surabaya, 2024)
The increasingly complex development of digitalization has made the government continue to develop electronic government as a form of accelerating bureaucratic reform. This applies to the Surabaya City Public Housing and Settlement Areas and Land of Surabaya City which has developed service innovations in the form of the E-Rusun platform. This technology-based platform or application is designed based on the needs of local governments to improve the quality of public services. One of the public services which is the task of DPRKPP is the management of flats with all the complexities faced, especially the administration of service administration. The presence of the E-Rusun platform is intended so that the community (users) get easy access to services without having to go through offline services. Furthermore, in the context of improving service quality, researchers want to sharpen the usefulness and impact of services that have been implemented through the E-Rusun platform in a study with a focus on innovation management used by E-Rusun platform developers. This research uses a qualitative approach with content analysis techniques. Content analysis is used to be able to sharpen each substance that will be reduced and compiled in the content analysis. The analysis was then carried out by building a content analysis matrix to get positive and negative sentiments from each substance of information obtained from sources and other supporting data. Data was collected through interview instruments, observation and documentation. The results of the analysis show that the application of E- Rusun application innovation in DPRKPP Surabaya City is good, it is proven by the improvement in the quality of flat management services in Surabaya City as seen from the number of services served: such as registration of flat permits/leases and flat payments faster and easier. However, the analysis also found technical problems such as: lack of understanding of the community in accessing the application due to the lack of socialization provided by DPRKPP Surabaya City. Thus, the recommendation that can be given by researchers is that the DPRKPP of Surabaya City needs to increase socialization to the community, especially flat residents.